Antibacterial Assay Of Cyperus rotundus Rhizomes Against Gram Positive And Gram Negative Bacteria: Uji Potensial Antibakteri Umbi Rumput Teki (Cyperus rotundus) terhadap bakteri Gram positif dan bakteri Gram negatif - Diana Yuni Anjarsari; Kinanti Ayu Puji Lestari (Journal Pharmasci (Journal of Pharmacy and Science), 2022)
Studies on antibacterial tests derived from natural ingredients were more intensively carried out. This was to reduce the side effects of using antibiotics related to the incidence of pathogenic bacteria. Nut grass tubers were one of the natural ingredients that are widely known for their benefits for human health. Nut grass tubers were also known to contain antibacterial compounds such as flavonoids, tannins, saponins and so on. This study aims to determine the potential of nut grass tuber extract as antibacterial of Gram positive and Gram negative. This study used a completely randomized design with the treatment of teki grass tuber extract with concentrations of 25%, 50% and 100%. Based on the research, it was known that the nut grass tubers were able to inhibit the growth of Gram positive and Gram negative bacteria in the category of weak to moderate ability. This study used the treatment of teki grass tuber extract with concentrations of 25%, 50% and 100%. Based on the research, it was found that the tuber of teki grass was able to inhibit the growth of Gram positive bacteria with the highest inhibition at 100% concentration of 5.53 mm and Gram negative with the highest inhibition at 100% concentration of 6.57 mm.